2018
DOI: 10.1021/acs.jproteome.8b00238
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dynamics of Proteome, Acetylome, and Succinylome during Stem-Cell Differentiation into Hepatocyte-like Cells

Abstract: Stem-cell differentiation is a complex biological process controlled by a series of functional protein clusters and signaling transductions, especially metabolism-related pathways. Although previous studies have quantified the proteome and phosphoproteome for stem-cell differentiation, the investigation of acylation-mediated regulation is still absent. In this study, we quantitatively profiled the proteome, acetylome, and succinylome in pluripotent human embryonic stem cells (hESCs) and differentiated hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A previous study found that STAT3 and STAT1 acetylation might be involved in hepatocyte proliferation in the Jak/STAT signaling pathway. 71 HBV X protein (HBX) is a viral protein encoded by a pregenomic RNA, which regulates VDAC3 activity. [72][73] VDAC3 is a voltagedependent anion channel that regulates Ca 2+ release and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that STAT3 and STAT1 acetylation might be involved in hepatocyte proliferation in the Jak/STAT signaling pathway. 71 HBV X protein (HBX) is a viral protein encoded by a pregenomic RNA, which regulates VDAC3 activity. [72][73] VDAC3 is a voltagedependent anion channel that regulates Ca 2+ release and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Untargeted proteomics , protein identification and quantification by liquid chromatography-tandem mass spectrometry (LC–MS/MS) were performed as previously 13 . In brief, the peptides were enriched by prewashed antibody beads (PTM Biolabs, Hangzhou, China), followed by analysis with tandem-mass-tag labeling combined with LC–MS/MS on the tissue samples.…”
Section: Methodsmentioning
confidence: 99%
“…The dramatic impact of these modifications on TCA and ETC proteins, along with the strong effect of histone succinylation, could very well in turn regulate the transition between the developmental states. Indeed, the differentiation of induced pluripotent stem cells (iPSCs) into hepatocyte-like cells was already proposed to be in part driven by a differential succinylation of proteins involved in the carbon metabolic pathways [ 64 ]. As detection methods for acylated peptides are only emerging, it would be of major interest to profile the succinylome of developing embryos or various pluripotent states to answer these questions.…”
Section: Regulatory Roles Of Intracellular Succinatementioning
confidence: 99%